Persepsi dan Sikap Mahasiswa Terhadap Nilai-Nilai Pancasila di Era Post-Truth: Studi Kualitatif pada Mahasiswa Pendidikan Pancasila dan Kewarganegaraan - Indrawati Syamsuddin (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the perceptions and attitudes of Pancasila and Civic Education (PPKn) students at Universitas Halu Oleo toward the values of Pancasila amid the post-truth phenomenon, and to describe how they respond to digital information that contradicts those values. A qualitative descriptive approach was employed, with data collected through in-depth interviews with eight active PPKn students and analyzed thematically. The findings show that students possess a conceptually mature perception of Pancasila values and a solid understanding of post-truth characteristics, largely shaped by their coursework. Indonesian Unity and Just and Civilized Humanity were perceived as the values most frequently challenged in digital spaces. In terms of attitude, students demonstrated a skeptical-reflective response pattern, applied layered verification strategies, and acted as informal digital-literacy educators for their peers and families. However, a "silent bystander" phenomenon was also identified among fellow students, indicating a gap between cognitive awareness and the courage to act. These findings suggest that strengthening conceptual understanding through Pancasila and Civic Education should be balanced with strengthening students' self-efficacy and constructive critical attitudes to face disinformation more effectively